Implementation of the Validity of the Belis System Marriage Related to the Reduction of Inheritance Rights on Land in Hambapraing Village, East Sumba Regency - Djae, Arnold Paul Kurniawan (PT. Anagata Sembagi Education, 2024)
Indonesia has cultural diversity that is reflected in marriage traditions, including belis, which is an important dowry in the customs of the people of Hambapraing Village, East Sumba Regency. Belis not only has a material value, but it is also symbolic, reflecting the appreciation and binding of the family relationship between the bride's family. Although national law through the Marriage Law regulates the conditions for the validity of marriage, traditional traditions such as belis are still considered valid if they meet the provisions of religious and state law. This study examines the validity of marriage with belis and its impact on inheritance rights, especially in patrilineal societies that prioritize boys as the main heirs. Girls generally receive a smaller share of the inheritance, depending on the gift from their parents or brother. Customary law is recognized by the 1945 Constitution and the UUPA, as long as it does not conflict with the national interest. With empirical legal research methods and conceptual approaches, this study combines primary and secondary data to analyze the interaction between customary law and national law. The results showed that marriage with belis was legally legal, with belis reflecting the value of nobility and family interaction in society.